2012
DOI: 10.1210/en.2012-1158
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti-Müllerian Hormone (AMH) During Follicle Development in a Monovulatory Species (Sheep)

Abstract: Knockout studies in mice have suggested that anti-Müllerian hormone (AMH) modulates primordial follicle recruitment and the response of growing follicles to FSH. Little is known of the physiology of AMH in monovular species, despite intense clinical interest in this factor. Using sheep as a model, we sought to investigate the functional role of AMH in modulating follicle development in monovular species. In contrast to the rodent, the results indicate that AMH does not affect the rate of primordial follicle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 41 publications
(54 reference statements)
4
74
2
1
Order By: Relevance
“…The results of this study also disagree with earlier results we have published utilizing an animal experimental model in which we found that DHEA supplementation significantly increased both serum AMH and follicular AMH protein expression (25). These differences, however, may be related to the fact that many of these effects in sheep were observed during the earlier stages of follicle development when AMH expression levels are high rather than in large ovulatory sized oestrogenic follicles in which AMH levels are known to be low (56,57).…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study also disagree with earlier results we have published utilizing an animal experimental model in which we found that DHEA supplementation significantly increased both serum AMH and follicular AMH protein expression (25). These differences, however, may be related to the fact that many of these effects in sheep were observed during the earlier stages of follicle development when AMH expression levels are high rather than in large ovulatory sized oestrogenic follicles in which AMH levels are known to be low (56,57).…”
Section: Discussioncontrasting
confidence: 99%
“…Among the factors implicated in early follicular development is AMH (Durlinger et al, 2002;Ireland et al, 2011;Campbell et al, 2012;Monniaux et al, 2014;Estienne et al, 2015). AMH is a dimeric glycoprotein member of the TGF-β superfamily (Rey et al, 2003;van Houten et al, 2010;Monniaux et al, 2014) and produced in granulosa cells from the primary follicle stage, increasing in preantral and small antral follicles, and gradually decreasing in mid-to large-antral follicles (Rico et al, 2011;Campbell et al, 2012).…”
Section: Anti-müllerian Hormone (Amh)mentioning
confidence: 99%
“…AMH is a dimeric glycoprotein member of the TGF-β superfamily (Rey et al, 2003;van Houten et al, 2010;Monniaux et al, 2014) and produced in granulosa cells from the primary follicle stage, increasing in preantral and small antral follicles, and gradually decreasing in mid-to large-antral follicles (Rico et al, 2011;Campbell et al, 2012). AntiMüllerian hormone knock-out studies in mice (Durlinger et al, 2002) and sheep (Campbell et al, 2012) have reported increases in the number of developing follicles suggesting that AMH is involved in both the regulation of transition from primordial into primary follicles (Gigli et al, 2005) and the rate of progression of gonadotropin-responsive to the gonadotropin-dependent stage. Furthermore, recent studies of follicle number and AMH in cattle have concluded that the inherently high variation in the ovarian reserve (Mossa et al, 2012), which is both heritable (Walsh et al, 2014) and also affected by maternal undernutrition (Mossa et al, 2013), has a negative impact on ovarian function that may result in suboptimal fertility (Ireland et al, 2011).…”
Section: Anti-müllerian Hormone (Amh)mentioning
confidence: 99%
“…Sertoli and granulosa cells express enzymes that cleave proAMH, with the levels of the enzymes and/or their regulators varying during testicular (Nachtigal & Ingraham 1996, Guo et al 2007, Le Magueresse-Battistoni 2007, Uhrin et al 2007) and ovarian (Bae et al 2008) development, the seminiferous cycle (Guo et al 2007, Le Magueresse-Battistoni 2007, Uhrin et al 2007, the ovarian cycle (Bae et al 2008, Wang et al 2014, the stage of ovarian follicular development (Ohnishi et al 2005, Bae et al 2008, Antenos et al 2011) and during pregnancy (Kwok et al 2013). However, the AMH in ovine follicular fluid is predominantly proAMH with little AMH N,C (Campbell et al 2012), suggesting that AMH can be synthesised and released with little or no prior cleavage. The enzymes that cleave proAMH have extracellular forms (Seidah et al 2006).…”
Section: Gonadal Cleavage Of Proamhmentioning
confidence: 99%